2011
DOI: 10.1109/tia.2011.2168931
|View full text |Cite
|
Sign up to set email alerts
|

Multicarrier Interleaved PWM Strategies for a Five-Level NPC Inverter Using a Three-Phase Coupled Inductor

Abstract: Multicarrier interleaved pulsewidth modulation (PWM) techniques are presented for a five-level neutral point clamped inverter using a three-phase coupled inductor. The inverter operation is demonstrated using a simple multicarrier interleaved PWM algorithm. Since both the inverter and inductor power losses are closely linked to the magnitude of the inductor current ripple, improved multilevel interleaved PWM techniques are presented based upon the concept of interchangeability of switching states in each phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…In the discontinuous ZSS an offset is added to the modulation index target in such a way that voltage generated at the VSC's output is clamped to a particular voltage level. In the literature it is shown that its possible to clamp the converter voltages over 30, 60, and 120 degrees intervals [33,34,47], and during those intervals the switching events are avoided [48,49]. The impact of the combination between the modulation techniques and the ZSS presented on the modular multilevel converter performance was also analyzed and presented in Section 4.…”
Section: Discontinuous Zss (D-zss)mentioning
confidence: 99%
“…In the discontinuous ZSS an offset is added to the modulation index target in such a way that voltage generated at the VSC's output is clamped to a particular voltage level. In the literature it is shown that its possible to clamp the converter voltages over 30, 60, and 120 degrees intervals [33,34,47], and during those intervals the switching events are avoided [48,49]. The impact of the combination between the modulation techniques and the ZSS presented on the modular multilevel converter performance was also analyzed and presented in Section 4.…”
Section: Discontinuous Zss (D-zss)mentioning
confidence: 99%
“…One of the configurations is the Neutral Point Clamped (NPC) multi-level inverter [5][6][7][8]. The distinct DC voltages are obtained by charging several capacitors from only one DC voltage source.…”
Section: Introductionmentioning
confidence: 99%
“…PWM interleaving methods and phase shift methods in the inverter were reported in the literature [9]- [11]. For reducing harmonics and improving torque density, usage of harmonic injection in 30 degree phase-shift 6-phase motor was also reported [12].…”
Section: Introductionmentioning
confidence: 99%